International money and finance - Hallwood, Paul C.; MacDonald, Ronald (Malden, MA : Blackwell Publishers, 2000)
Business
Keywords: International finance; Macroeconomics; International policy; Exchange rate; Currency; Monetary unions; International monetary fund; International debt